Grundtvig og Rasmus Sørensen. Anmeldelse af Knud Bannings "Landsbylærer" og "Degnekristne" - Bugge, Knud Eyvin (Grundtvig-studier, 1959)
Summary of the Review of Knud Banning9s Books.Grundtvig and Rasmus Sørensen. By Knud Eyvin Bugge.This article is a review of two books by Knud Banning - “A Village Teacher” and “ Christian Deacons” (both published in Copenhagen, 1958), the latter of which is a thesis for a Doctor’s Degree. The books are of interest for readers of “ Grundtvig Studies”, on the one hand because they give an insight into important events and currents of thought during Grundtvig’s lifetime, and besides this they also give a detailed description of Grundtvig’s relations with Rasmus Sørensen, who was a leading figure in the so-called “religious awakening” in South-west Sjaelland in the i 83o’s.Rasmus Sørensen was bom in 1799 and was trained as a teacher at Vesterborg Seminary in Lolland. All his life was influenced by his stay in these surroundings, where the best-known names were those of Bishonp P. O. Boisen and Count G. D. Reventlow, the famous champion of the emancipation of the peasants at the end of the 18th century. Under the influence of thi circle and its distinctive characteristics, Rasmus Sørensen became convinced that it was the chief task of the village school to contribute to the emancipation of the peasantclass, in both the social and the religious sphere. In reality his struggle became in essence a conflict with the clergy. Banning’s merit is to have shown how these religious and social viewpoints are combined in an indissoluble unity in Rasmus Sørensen’s struggle.Rasmus Sørensen first became acquainted with Grundtvig through his books. Reading Grundtvig’s “ Biblical Sermons” ( 1816) brought about a crisis of conversion for Rasmus Sørensen, and he became a whole-hearted adherent of the orthodox Lutheran views which Grundtvig then held. He entered into a correspondence with Grundtvig, and visited him a couple of times at Praestø. Their relationship did not continue without some friction, because, among other things, Grundtvig’s thought in the 1820’s and 1830’s developed away from his earlier standpoint. No break took place, however, until 1836. Its occasion was the already well-known dispute between Rasmus Sørensen and Grundtvig concerning their views on the question as to how far it is the school’s task to instil the Christian faith into the children. Rasmus Sørensen answered the question in the affirmative and Grundtvig in the negative, and thereupon Rasmus Sørensen bade farewell to Grundtvig in a letter quivering with indignation. Still, he could not wholly tear himself loose from the influence of Grundtvig’s ideas, but continued for many years afterwards to discuss them in his writings.Rasmus Sørensen’s relationship to the religious awakening in South-west Sjaelland became for various reasons increasingly strained. He therefore gave up his teaching post in 1844, and turned to political activities. In 1852 he emigrated to America, and he died in 1865 while staying for a while in Denmark.